Derivational Morphemes in Selena Gomez’s Speech - Dewi, Ni Luh Desy Utari; Sukarini, Ni Wayan; Putra, I Komang Sumaryana (CV. Ulil Albab Corp, 2024)
English is the most widely spoken language worldwide for social, economic, political, cultural, technological, and educational communication. Along these lines, when people learn vocabulary of English, they will find countless different words, from littlest to biggest word, they are derivational morphemes of an English word. Therefore, it is interesting in discussing the derivational process that exists in Selena Gomez’s Speech. Descriptive qualitative methods are used in this research to analyzed the derivational morpheme and the functions of derivational morpheme in Selena Gomez’s Speech. The data was collected using documentation method and note taking technique through, reading carefully, highlighting, classifying the types and the function. The collected data was analyzed using qualitative method and explained descriptively. This research applied the morphology theory proposed by Katamba (1993) in order to identify the types and functions of derivational morpheme in Selena Gomez’s Speech.